DIALECTIC BASIS OF THE INFLUENCE OF NATIONAL IDENTITY AND HISTORICAL MEMORY ON SOCIAL MENTALITY (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the concept of social mentality and its role in the development of society from a socio-philosophical perspective. The study examines the main factors influencing the transformation of social mentality, including socio-economic, political-legal, spiritual-educational, information-communication, and historical-cultural factors. It is argued that the harmonious combination of national values, historical memory, and modern reforms plays an important role in the renewal of social mentality.